Utility of Serum Neopterin and Serum IL-2 Receptor Levels to Predict Absolute CD4 T Lymphocyte Count in HIV Infected Cases - Chadha, Sanjim; Bhalla, Preena; Gautam, Hitender; Chakravarti, Anita; Saini, Sanjeev; Anuradha, S.; Dewan, Richa (Interdisciplinary Perspectives on Infectious Diseases, 2013)
A prospective study was carried out to evaluate the efficacy of serum neopterin and soluble IL-2 receptor (sIL-2R) concentrations in comparison to CD4 count to study the progression of HIV disease and monitor response to ART in HIV cases. One hundred newly diagnosed HIV seropositive subjects were recruited. CD4 counts were determined by FACS system. Serum neopterin and sIL-2R levels were measured using enzyme immunoassay. In our study, levels of neopterin and sIL-2R were significantly higher in subjects with CD4 <200 cells/μL (with S. neopterin levels of >25.1 nmol/L and sIL-2R levels of >47.1 pM as cutoff values for CD4 <200 cells/μL) compared to those in subjects with CD4 >200 cells/μL at baseline which indicate that these markers can be utilized for initiation of ART in HIV cases. The levels of these markers decreased significantly after initiation of ART. In patients with CD4 >200 cells/μL, these markers are helpful in predicting disease progression.